CORRELATION OF FINANCING MANAGEMENT TOWARDS THE QUALITY OF EDUCATION IN MADRASAH DINIYAH TAKMILIYAH AWALIYAH IN BANDUNG DISTRICT - Badrudin Badrudin; Neng Gustini; Cep Ilyas Amirulloh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to determine and describe the relationship between financing management and the quality of diniyah education in Madrasah Diniyah Takmiliyah Awaliyah in the Bandung Regency. This study uses a quantitative approach. The data collection technique is done by distributing questionnaires (questionnaires) and documentation with a sample of 37 people. The data analysis techniques used are research instrument trials, partial analysis, correlation analysis, and coefficient of determination (contribution) analysis. The results showed that the achievement of financing management and the quality of diniyah Takmiliyah Awaliyah education in Bandung Regency showed a significant relationship between financing management and the quality of diniyah education. The linearity test of financing management (X) and the quality of diniyah education (Y) obtained a value of F = 1.611 with a significance level of 0.218, so it can be interpreted that it has a positive and significant linear relationship. This study has implications for the importance of effective financing management in improving the quality of madrasah.